2022
DOI: 10.1371/journal.pgph.0000135
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and other risk factors for esophageal squamous cell carcinoma in Lilongwe Malawi: Results from the Lilongwe esophageal cancer case: Control study

Abstract: Objective Esophageal cancer is the second commonest cancer in Malawi, and 95% of all cases are esophageal squamous cell carcinoma (ESCC). Very little is known about the epidemiology of ESCC in Malawi including risk factors. The main objective of the study was to evaluate and describe risk factors of ESCC in Malawi. Methods We conducted a case-control study from 2017 to 2020 at two hospitals in Lilongwe, Malawi and consenting adults were eligible for inclusion. Endoscopy was conducted on all cases and biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…Previous studies in Malawi found published in 2015 and 2022 an OR of 5.4 (95%CI 2.0‐15.2) and 2.4 (95%CI 1.4‐4.2) for cigarette smoking 21,22 . Two previous studies from Kenya, published in 2013 23 and 2015 24 both showed that tobacco smoking had an increased odds of ESCC risk of 2.5‐fold and 5%, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies in Malawi found published in 2015 and 2022 an OR of 5.4 (95%CI 2.0‐15.2) and 2.4 (95%CI 1.4‐4.2) for cigarette smoking 21,22 . Two previous studies from Kenya, published in 2013 23 and 2015 24 both showed that tobacco smoking had an increased odds of ESCC risk of 2.5‐fold and 5%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in Malawi found published in 2015 and 2022 an OR of 5.4 (95%CI 2.0-15.2) and 2.4 (95%CI 1.4-4.2) for cigarette smoking. 21,22 Two previous studies from Kenya, published in 2013 23 and 2015 24 both showed that tobacco smoking had an increased odds of ESCC risk of 2.5-fold and 5%, respectively. In our study, data from Malawi and Kenya showed that smoking rolled cigarettes had a relatively stronger association to ESCC development, compared to never smokers (Table 3).…”
Section: Comparison With Previous Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…We used a structured questionnaire based on a mobile platform and delivered by trained research personnel to measure known or suspected ESCC risk factors, including history of tobacco smoking, alcohol consumption, household solid fuel use for heating, main source of cooking fuel, consumption of moldy grain, consumption of hot tea, socioeconomic status (SES), HIV status, geophagia (eating soil) and history of esophageal cancer among siblings, as described previously. 17 Tobacco smoking was defined as regular use of tobacco in any form at least once a week for a period of 6 months in one's lifetime. We further classified the type of tobacco regularly used as selfrolled cigarettes, shop-bought cigarettes, self-rolled and shop-bought cigarettes or other forms of tobacco.…”
Section: Assessment Of Escc Risk Factorsmentioning
confidence: 99%
“…14,15 The exact mechanisms of these associations between oral health and ESCC are not understood but are hypothesized to involve the oral microbiome. 16 We conducted a case-control study to examine the etiology of ESCC in Malawi, 17 and here we examined the relationship between poor oral health and ESCC risk in this study population. Oral health was assessed using multiple measures, including the sum of decayed, missing or filled teeth (DMFT score); dental fluorosis; oral mucosa status; lip depigmentation and toothbrushing method and frequency.…”
Section: Introductionmentioning
confidence: 99%